Laser-assisted-autoionization dynamics of helium resonances with single attosecond pulses - Chu, Wei-Chun; Zhao, Song-Feng; Lin, C. D. (My University, 2011)
The strong coupling between two autoionizing states in helium is studied theoretically with the pump-probe scheme. An isolated 100-as XUV pulse is used to excite helium near the 2s2p(1P) resonance state in the presence of an intense infrared (IR) laser. The laser field introduces strong coupling between 2s2p(1P) and 2p2(1S) states. The IR also can ionize helium from both autoionizing states. By changing the time delay between the XUV and the IR pulses, we investigated the photoelectron spectra near the two resonances. The results are used to explain the recent experiment by Gilbertson et al. [Phys. Rev. Lett. 105, 263003 (2010)]. Using the same isolated attosecond pulse and a 540-nm laser, we also investigate the strong coupling between 2s2p(1P) and 2s2(1S) by examining how the photoelectron spectra are modified versus the time delay and the possibility of observing Autler-Townes doublet in such experiments.